Germ Cell Neoplasia in situ (GCNIS) in Testis-Sparing Surgery (TSS) for Small Testicular Masses (STMs) - Pierconti, Francesco; Martini, Maurizio; Grande, Giuseppe; Larocca, Luigi M.; Sacco, Emilio; Pugliese, Dario; Gulino, Gaetano; Bassi, Pier F.; Milardi, Domenico; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2019)
Purpose: The testis-sparing surgery (TSS) is surgical technique acceptefor small testicular masses (STMs). Frozen section examination (FSE) is an essential assessment at the time of TSS. The aim of this study is to measure the maximum distance of the foci of ITGCN from STMs. Methods. In our hospital between June 2010 and October 2017 a total of 68 patients with STM underwent a TSS. All the testis specimens were totally embedded and processed via the whole-mount method and a diagnosis of germ cell tumor with GCNIS were made. The distance between STMs and GCNIS were calculated by two pathologists directly on the slides considering for the third dimension the number of the paraffin blocks in which the foci of GCNIS were found. Results. The STMs were classic seminoma in 62 out 68 cases, embryonal carcinoma in 4 cases, while in 2 case a diagnose of mixed germ cell tumor were made. The size of the STMs was between 0,5 cm and 2 cm and the foci of GCNIS were observed in seminiferous tubules very closed to SMTs or as skip lesions in the surrounding testicular parenchyma, dispersed in normal testis. In 48 out of 68 cases (70,5% ) foci of GCNIS were at the distance from SMTS of 1,5 cm or below and in 60 out of 68 cases (88%) at the distance of 2 cm or below The distance of GCNIS from the STMs was not related to the histological subtype of the germ cell tumor, while there is a linear correlation between size of the STMs and the distance of foci of GCNIS (p=0,0105; r=0,9167). Conclusion: Our data showed that foci of ITGCN were not observed beyond 2,5 cm from the STM. In particular we demonstrated that exist a linear correlation between size of STMs and distance of the foci of GCNIS from STMs (p=0,0105; r=0,9167). In conclusion mapping the tissue around the tumour not randomly but in targeted areas could reduce the false negative biopsies of the testis with GCNIS, increasing the radicality of the TSS procedure.